035 Vestibular syndrome: a single centre experience of acute dizziness. Issue 6 (27th May 2022) - Mahmud, Mohammad; Prendergast, Mabel; Dixon, Luke; Seemungal, Barry
Abstract : Dizziness accounts for 2–5% of emergency department presentations. Vestibular syndrome, one cause of dizziness, can present secondary to an acute stroke of the brainstem and cerebellar (posterior circula- tion), a life-threatening condition that has potential time dependent treatments. We conducted a retrospective case note analysis using Imperial NHS Trust patient records from January to September 2020. We looked at presentations of all presentations of vestibular syndrome requiring MRI head imaging. Retrospective ethics were obtained from local ethics committee. 116 patient encounters (54% female) were included with a mean (SD) age of 62 (±18). DWI-positive stroke was confirmed in 23% of patients presenting with acute dizziness. Of these DWI-positive stroke patients, a further 23% presented with isolated vertigo. The mean NIHSS score of isolated vertigo patients was 0 and none underwent thrombolysis. Only 14% of patients had a complete HINTS examination and none were referred to the Neuro-Otology Unit. The isolated vertigo patients who were DWI-negative had no definitive diagnosis in 45% of the patient encounters. Major deficiencies exist in the care of patients presenting with dizziness, especially stroke patients. There is a need for stroke clerking to include dizziness and for doctors to be aware of stroke presenting as isolated vertigo. mabel.prendergast18@imperial.ac.uk